Odpowiedź :
14.
[tex]a)\\(3x-2)(x+1) = 3x^{2}-5\\\\3x^{2}+3x-2x-2 = 3x^{2}-5\\\\x = -5+2\\\\x = -3[/tex]
[tex]b)\\(4-5x)(2+x) = -(4+5x^{2})\\\\8 + 4x - 10x -5x^{2} = -4-5x^{2}\\\\-6x+8 = -4\\\\-6x = -4-8\\\\-6x = -12 \ \ /:(-6)\\\\x = 2[/tex]
Odpowiedź:
a) (3x - 2)(x+1)=3x^2 - 5
3x^2+3x - 2x - 2=3x^2 - 5
3x^2 - 3x^2+3x - 2x= - 5+2
x= - 3
b) (4 - 5x)(2+x)= - (4+5x^2)
8+4x - 10x - 5x^2= - 4 - 5x^2
- 5x^2+5x^2+4x - 10x= - 4 - 8
- 6x= - 12/:( - 6)
x=2
c) 4x^2 - 2x=(2x+1)(2x - 3)
4x^2 - 2x=4x^2 - 6x+2x - 3
4x^2 - 4x^2 - 2x+6x - 2x= - 3
2x= - 3/:2
x= - 3/2
d) 3x(2x+5)=(x+3)(6x+1)
6x^2+15x=6x^2+x+18x+3
6x^2 - 6x^2+15x - x - 18x=3
- 4x=3/:( - 4)
x = - 3/4
Szczegółowe wyjaśnienie: